The inhibitory effect of 6-gingerol and cisplatin on ovarian cancer and antitumor activity: In silico, in vitro, and in vivo - Salari, Zohreh; Khosravi, Ahmad; Pourkhandani, Elham; Molaakbari, Elaheh; Salarkia, Ehsan; Keyhani, Alireza; Sharifi, Iraj; Tavakkoli, Hadi; Sohbati, Samira; Dabiri, Shahriar; Ren, Guogang; Shafie’ei, Mohammad (Frontiers in Oncology, 2023)
Background: Epithelial ovarian cancer is very common in women and caused hundreds of deaths a year worldwide. The chemotherapy drugs including cisplatin had adverse activity on patients’ health. Complementary treatments and the use of herbal medicines can play an important role in improving the performance of medicine. 6-gingerol is the major pharmacologically-active component of ginger. In this study, we compared the effects of 6-gingerol, cisplatin, and their mixture in apoptosis and angiogenesis activity in silico, test-tube, and in vivo assays against two ovarian cancer cell lines: OVCAR-3 and umbilical cord endothelial cells (HUVEC). Methods: The drug-treated cell lines were evaluated for their cytotoxicity, cell cycle, and apoptotic and angiogenetic gene expression changes. Results: The proportion of apoptosis treated by the 6-gingerol coupled with cisplatin, was significantly high. In the evaluation of the cell cycle, the combination therapy also showed a significant promotion of a higher extent of the S sequence. The expression of P53 level, caspase 8, Bax, and Apaf1 genes were amplified again with combination therapy. Conversely, in both cell lines, the cumulative drug concentrations reduced the expression of VEGF, FLT1, KDR, and BCL-2 genes. Similarly, in the control group, combination treatment significantly decreased the expression of VEGF, FLT1, KDR, and BCL-2 genes in comparison to cisplatin alone. Conclusions: The findings of the present study demonstrated that the cisplatin and 6-gingerol combination can be more effective in inducing apoptosis and suppressing the angiogenesis of ovarian cancer cells than that of each drug alone.